Alfalfa hay supplement as compared to fish liver oil in the vitamin A nutrition of eastern Colorado beef cattle - Kniese, Marvin E, author; Washburn, L. E., advisor; Wheeler, S. S. (Sherman Shaw), 1901-, committee member; Stonaker, Howard H., committee member; Bourne, Richard F., committee member; Jensen, Rue, committee member; Frey, Paul Reheard, committee member (Colorado State University. Libraries, 1947)
To view the abstract, please see the full text of the document.
Keywords: Feeds